Quantitative study of mucosal structure, enzyme activities and phenylalanine accumulation in jejunal biopsies of patients with early and late onset diabetes. Issue 11 (November 1979) - Riecken, E O; Zennek, A; Lay, A; Menge, H
Abstract : A study of the three-dimensional structure of the upper jejunal mucosa in diabetics has been carried out. The structural findings were related to 14C-L-phenylalanine uptake in vitro, sucrase activity in mucosal homogenates, and the enzyme content of the absorptive cells as measured cytophotometrically. A low grade mucosal transformation of the sprue-type was found, which was associated with decreased sucrase activity, and with no reduction in phenylalanine accumulation. On the other hand the specific activities of alkaline phosphatase, non-specific esterase, and succinic dehydrogenase in the surface cells remained unchanged.